Defective thyroid hormone transport to the brain leads to astroglial alterations - Guillén-Yunta, Marina; García-Aldea, Ángel; Valcárcel-Hernández, Víctor; Sanz-Bógalo, Ainara; Muñoz-Moreno, Emma; Matheus, Maria Gisele; Grijota-Martínez, Carmen; Montero-Pedrazuela, Ana; Guadaño-Ferraz, Ana; Bárez-López, Soledad (Neurobiology of disease, 2024)
Allan-Herndon-Dudley syndrome (AHDS) is a rare X-linked disorder that causes severe neurological damage, for which there is no effective treatment. AHDS is due to inactivating mutations in the thyroid hormone transporter MCT8 that impair the entry of thyroid hormones into the brain, resulting in cerebral hypothyroidism. However, the pathophysiology of AHDS is still not fully understood and this is essential to develop therapeutic strategies. Based on evidence suggesting that thyroid hormone deficit leads to alterations in astroglial cells, including gliosis, in this work, we have evaluated astroglial impairments in MCT8 deficiency by means of magnetic resonance imaging, histological, ultrastructural, and immunohistochemical techniques, and by mining available RNA sequencing outputs. Apparent diffusion coefficient (ADC) imaging values obtained from magnetic resonance imaging showed changes indicative of alterations in brain cytoarchitecture in MCT8-deficient patients (n = 11) compared to control subjects (n = 11). Astroglial alterations were confirmed by immunohistochemistry against astroglial markers in autopsy brain samples of an 11-year-old and a 30th gestational week MCT8-deficient subjects in comparison to brain samples from control subjects at similar ages. These findings were validated and further explored in a mouse model of AHDS. Our findings confirm changes in all the astroglial populations of the cerebral cortex in MCT8 deficiency that impact astrocytic metabolic and mitochondrial cellular respiration functions. These impairments arise early in brain development and persist at adult stages, revealing an abnormal distribution, density, morphology of cortical astrocytes, along with altered transcriptome, compatible with an astrogliosis-like phenotype at adult stages. We conclude that astrocytes are potential novel therapeutic targets in AHDS, and we propose ADC imaging as a tool to monitor the progression of neurological impairments and potential effects of treatments in MCT8 deficiency. [Display omitted] •MRI ADC values suggest defects in brain cytoarchitecture in MCT8-deficient patients.•MCT8-deficient astroglia shows altered distribution, density and morphology.•MCT8 deficiency affects astrocytic metabolism and mitochondrial cellular respiration.•Astroglial alterations arise early in brain development and respond to brain damage.•Astroglial alterations arise as a new pathological mechanism in MCT8 deficiency.